Principal Guidance for Teachers at SD Negeri Citalaksana in Creating Illustrated Stories Using the Canva Application - Nur Endah Sariningsih; Ineu Kenanga Dewi (al-Afkar, Journal For Islamic Studies, 2026)
Picture stories not only help students understand concepts better, but also stimulate their imagination and creativity. The methods used in this PkM activity are lectures, questions and answers and group discussions as well as direct practice using a laptop. From the results of these PkM activities, to improve teachers' skills in using the Canva application, through structured and direct practice-based training, teachers can improve their skills in using the Canva application. The results of these activities are used to assist teachers in designing interesting materials, where this training facilitates teachers to design more interesting learning materials by utilizing existing features.